2016
DOI: 10.3177/jnsv.62.141
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Supplements to Stimulate Lipolysis: A Review in Relation to Endurance Exercise Capacity

Abstract: Athletes make great efforts to increase their endurance capacity in many ways. Using nutrition supplements for stimulating lipolysis is one such strategy to improve endurance performance. These supplements contain certain ingredients that affect fat metabolism; furthermore, in combination with endurance training, they tend to have additive effects. A large body of scientific evidence shows that nutrition supplements increase fat metabolism; however, the usefulness of lipolytic supplements as ergogenic function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 173 publications
(174 reference statements)
0
46
0
4
Order By: Relevance
“…Investigating novel diet‐exercise interactions holds relevance for the sports nutrition sphere, as optimizing metabolic and training adaptations to exercise is a critical determinant of athletic performance . Moreover, current literature has assessed the efficacy of combining nutritional and exercise interventions to improve metabolic health biomarkers including insulin sensitivity, glucose, and lipid metabolism …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigating novel diet‐exercise interactions holds relevance for the sports nutrition sphere, as optimizing metabolic and training adaptations to exercise is a critical determinant of athletic performance . Moreover, current literature has assessed the efficacy of combining nutritional and exercise interventions to improve metabolic health biomarkers including insulin sensitivity, glucose, and lipid metabolism …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Moreover, current literature has assessed the efficacy of combining nutritional and exercise interventions to improve metabolic health biomarkers including insulin sensitivity, glucose, and lipid metabolism. 3,4 Recently, fasting-based interventions such as intermittent fasting have garnered interest as alternatives to conventional dietary strategies for improving metabolic biomarkers in both healthy and clinical populations. 5,6 This is based on the hypothesis that such interventions act on similar biological pathways to conventional methods, while potentially being a more feasible long-term approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbohydrate and fat metabolism occur in the muscles during exercise [14]. Skeletal muscles generate energy using energy sources source such as glucose, lactate, and fatty acids [4, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Several animal studies showed that acute capsaicin supplementation was e cient to improve endurance capacity (exercises protocols between 30-60 minutes of moderate aerobic exercise) (Kim et al, 2016). It might be related in part to an increase in hepatic glycogen content, being considered an important mechanism for energy homeostasis and via activation of TRPV1 due to capsaicin supplementation and improvements of energy metabolism by increasing lipolysis saving and maintaining muscle glycogen reserves (Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%